PERALIHAN HAK ATAS TANAH TANPA MELALUI PEJABAT PEMBUAT AKTA TANAH BERDASARKAN PUTUSAN PENGADILAN (PERKARA NOMOR:156/Pdt.G/2011/PN.PBR) - Radius Lase; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Under the terms of the applicable purchase of land rights must be donebefore PPAT but in everyday life was still a lot going on transfer of rights on landthat was done under the hand in the sense of not carried out according toregulations, such things surely would be very detrimental to the buyer , becausehe can only control the rights to land just physically but not legally. Last holdersrequesting decisions regarding selling without PPAT deed, the District CourtPekanbaru used as the basis for recording a transfer rights in the District LandOffice / Municipality.This research method used is normative. Normative law research method isthe method or methods used in legal research done by examining existing librarymaterials. This study discusses the law synchronizing data used is secondary data,ie data that support the information or support the completeness of the primarydata is done by means of literature or literature. Data analysis used the normativequalitative analysis presented in narrative form further analyzed to obtain claritysettlement of the problem, then the conclusions drawn deductively, from the thingsthat are common toward the things that are special.Results from this study is the Basic Legal Considerations Pekanbaru DistrictCourt Judge Case Number: 156 / Pdt.G / 2011 / PN. PBR is not yet synchronized,since the court decision has permanent legal force, it has the same effect andfunction of the deed of sale made by PPAT.Consequently Court Decision No. 156 / Pdt.G / PN.Pbr can be used asevidence to be recorded in the land book and flipped called a certificate on behalfof the buyer. land court judge in the District Court should be the Chairman shouldbe able to issue a "determination", not a "decision". Court Decision No. 156 /Pdt.G / PN.Pbr and binding is used as a basis for the transfer of land rightsrecorded in the land book and flipped called a certificate on behalf of the buyer aslast rights holders so that the rights of the buyer gets legal certainty on the land.Keywords: Transfer of Rights, Court Decisions, Purchase